Analysis of Impoliteness Strategies Used in Putin's Speech at Annexation Ceremony - Yaseen Hassan, Aalaa; Firas Abdullah Al-Rawe, Marwah; Shamel Abdullah , Shaden; Hlaimi, Stéphane (UIN Salatiga, 2023)
This study aims to investigate the types of impoliteness strategies used in Putin's speech at the annexation ceremony. All of Putin's speeches were intentionally delivered to cause damage to the hearers' negative and positive faces. Culpeper's (2011) classifications of impoliteness, which consist of five strategies that are the opposite of politeness, were adopted. Both qualitative and quantitative analyses have been used to accomplish the study objectives. Putin mostly used the negative impoliteness strategy, directly attacking the West and their policies. Furthermore, he considered his authority to be higher than Kyiv and the West, and for this reason, he insulted, belittled, blamed, and accused them. In several texts, he used